INDISCIPLINE AND SCHOOL REPETITION: THE INTRICACIES OF A RELATIONSHIP - Silva Neto, Cláudio Marques da (2023)
In this article, we present some results of an ethnographic study on indiscipline in the classroom,  more specifically analyzing the observed concomitance between students' disciplinary conduct and their chances of failing. We analyze this occurrence from a perspective that combines classic sociological variables, such as sex/gender, social class and color/race of students with others more specific to the school context, such as the disciplinary environment and the teacher-student relationship. We problematize the nature of the social interaction process in the classroom, which tends to assign male students with a greater propensity for divergent disciplinary conduct while assuming that it is natural for girls to accept the incorporated forms of the school order. The results show significant differences in the forms of indiscipline practiced by boys and girls, as well as revealing that the more challenging behavior of male students profoundly affects the teacher-student relationship, to the point of affecting the school trajectory of some of them, even in the case of students who manage to reconcile indiscipline with a good performance in studies.